PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PERHOTELAN B3 PADA MATA PELAJARAN SENI BUDAYA BERKREASI SENI TARI DARI KARYA SENI BENTUK LAIN DI SMK NEGERI 3 DENPASAR - I Made Sujana; Ni Putu Elma Rahayu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to determine the learning outcomes of class X students in hospitality B3 in the subject of Cultural Arts by applying the 2022/2023 Project Based Learning (PjBL) model. This research method uses Classroom Action Research which is carried out in two cycles with each cycle consisting of planning, implementation, action, observation and reflection. The subjects of this study were students of class X Hospitality B3 with a total of 39 students. The results of this study are increased learning outcomes in the subject of Cultural Arts Creative dance from other forms of art. This is evidenced by the increase in student learning outcomes in the first cycle and the second cycle has increased. In Cycle I the number of students who completed 24 students (61.54%) with an average score of student learning outcomes reached 75.32. 61.54% did not meet the specified classical completeness, namely 75% of the total number of students. Whereas in cycle II the number of students who passed experienced an increase of 39 students (100%) with an average student score of 80.61. Based on the results of this study it can be concluded that by implementing the Project Based Learning (PJBL) learning model it can improve the learning outcomes of class X Hospitality B3 at SMK Negeri 3 Denpasar